Synthesis of Activated Carbon Mesoporous from Coffee Waste and Its Application in Adsorption Zinc and Mercury Ions from Aqueous Solution - Liliana Giraldo; Juan Carlos Moreno-Piraján (E-Journal of Chemistry)
We obtain activated carbons with high portion of meso pores using coffee residues as precursor for the application of adsorption of large adsorbates. Because of its natural properties, the coffee residue exhibited a large pore size. In this work, the coffee residue were impregnated with ZnCl2 and KOH, and then carbonized under the nitrogen conditions and activated with CO2 respectively. Obtained activated carbons are used in the adsorption of ions Hg(II) and Zn(II). These adsorbents are efficacious to remove these ions from aqueous solution, with monocomponent equilibrium adsorption capacities ranging from from 0.002 to 0.380 mmol∙g-1 for Hg on ACK3 and from 0.002 to 0.330 mmol∙g-1 for ACZ3. For Zn(II) on ACK2 from 0.002 to 0.300 mmol∙g-1, and from 0.001 to 0.274 mmol∙g-1 for ACZ2.